Splošne knjižnice po knjižničnih območjih v letu 2009 - Bon, Milena (Knjižnica, 2011)
Purpose: Regional public libraries were initiated in 2003 to connect professional activities of libraries within regional networks and to ensure coordinated library development in a region in cooperation with the Library system development centre at the National and university library performing a coordinating role. The article analyses the performance of public libraries and their integration in regional library networks in order to find out the level of development of conditions of performance of public libraries. Methodology/approach: Statistical datafor the year 2009 were the basis for the overview of library activities of ten library regions with regard to applicable legislation and library standards. The level of regional library activities is compared to the socio-economic situation of statistical regions thus representing a new approach to the presentation of Slovenian's public libraries' development. Results: Absolute values indicate better development of nine libraries in the central Slovenia region while relative values offer a totally different picture. Four libraries in the region of Nova Gorica prove the highest level of development. Research limitation: Research is limited to the year 2009 and basic statistical analysis. Originality/practical implications: Findings of the analysis are useful for public libraries to plan their development strategy within a region and for financial bodies to provide for adequate financing for library activities in a specific region. The basic condition for successful public library performance is the even and harmonized development of conditions of performance as recommended by library standards.
Keywords: splošne knjižnice; osrednje območne knjižnice; knjižnične mreže; Slovenia; Slovenija